2022
DOI: 10.1123/ijatt.2020-0079
|View full text |Cite
|
Sign up to set email alerts
|

Wetted Ice With Elastic Wrap Decreases Intramuscular Temperature More Quickly Than Game Ready®

Abstract: Cryotherapy is a popular treatment chosen by health care providers to treat musculoskeletal injuries. The purpose of this study was to determine which cryotherapy method, Game Ready® or a wetted ice bag with elastic wrap, caused a greater and faster decline in tissue temperature during a 30-min treatment. At 2 cm below adipose, intramuscular tissue temperatures decreased more and faster with the wetted ice treatment compared with the Game Ready® treatment at all three time points: 10 min, 20 min, and 30 min. F… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 10 publications
0
1
0
Order By: Relevance
“…Patients randomised to the GR group were provided their own leg wrap which they used for the duration of their intervention (2 weeks). Prior research has found there to be 2.5°-3.5° difference 1 3 in intramuscular temperatures between the two modalities, with crushed ice providing more cooling [2,12]. In these studies, the ice was directly applied onto the skin, hence by applying the tubigrip under the ice we aim to eliminate this temperature difference.…”
Section: Usual Care (Uc) and Game Ready (Gr) Treatment Protocolsmentioning
confidence: 99%
“…Patients randomised to the GR group were provided their own leg wrap which they used for the duration of their intervention (2 weeks). Prior research has found there to be 2.5°-3.5° difference 1 3 in intramuscular temperatures between the two modalities, with crushed ice providing more cooling [2,12]. In these studies, the ice was directly applied onto the skin, hence by applying the tubigrip under the ice we aim to eliminate this temperature difference.…”
Section: Usual Care (Uc) and Game Ready (Gr) Treatment Protocolsmentioning
confidence: 99%